PERFORMANCE EVALUATION OF DNA PATTERN MATCHING ALGORITHMS - I. Aziz; S.Shoaib; K.S.Khurshid; T.Ahmad; M.Awais (Pakistan journal of science, 2023)
Bioinformatics is a new area of research in which DNA, RNA and proteinssequences are dealt. To store, retrieve, analyze, match, align, search, and process these sequencesdifferent techniques are existed. Currently a lot of advancements in sequence analysis cause the drasticincrease in the DNA database sizes that require more efficient approaches encompass accuracy. Searchand analysis of DNA patterns can be performed by using various pattern matching algorithms in thecomputational biology. The aim of present study is to present taxonomy and performance evaluation ofthese pattern matching algorithms. The objective of this SLR is to set a research trend and to find amathematical model to estimate execution search time before scanning whole DNA sequence byfollowing a search strategy.